Effectiveness of vermi composting in management of organic waste at central zoo jawalkhel and its relevancy to hattisar management in Nepal. - Dhimal, Meghnath (2006)
ABSTRACT: This research is an attempt to identify the amount and composition of daily waste generation in the Central Zoo and potential role of vermicomposting on management of organic wastes of animals at central Zoo. The study design was cross-sectional as well as cash-control intervention study. This study was carried out from May 2004 to January 2005. The daily waste generation in Central Zoo was calculated 640 kg per day during the study. The highest amount of waste generation was of animals followed by litter and garbage. The waste composition was divided into six groups, animal waste, litter and garbage, plastics, metal/glass, meat and paper. The study revealed that animal waste (56.20%), litter and garbage (40.59%), plastics (0.93%), metal/glass (0.54%), meat (0.7%) and paper (0.9%). From this study we can say that about 97% waste can be converted into compost. Hence composting can be the best option for the waste management in the Central Zoo. The elephant dung, rhino dung and litter and garbage, each of 50kg were vermicomposted using the two earthworm species Eisenia foetida and Perionyx species. The compost was prepared in 42 days, 56 days, and 75 days respectively for elephant, rhino and litter and garbage waste. The organic matter, Nitrogen, Phosphorus, Potassium value was increased in elephant vermicompost compared to elephant dung but the NPK value and organic matter content was decreased in rhino vermicompost compared to rhino dung. The analysis of variance of nutrient contents in vermicompost of different sources showed the significantly different at 5% levels of significance. The multiple comparisons of means also showed significant difference result. The application of the compost in the experimental crops Brassica oleraceae local cultivars did not give significantly higher yield as well as the number of leaves per plant was not significantly different. The application of the compost on the potting test on potato (Solanum tubersom), gave the significantly different yield at 5% levels of significance. The residual effect of compost on rooftop gardening for flowers and garlic also gave good result. If the roof top green gardening is practiced in urban areas it helps to make the urban areas more livable and sustainable by increasing the urban food production and reducing climate change. The water quality monitoring of central Zoo using physic-chemical and benthos faunas revealed that water was moderately polluted. Key Words: Vermicomposting, Zoo, Dung, Compost, Productivity, physic-chemical